The Effects of Sequestration on Indian Health - Malerba, Marilynn (The Hastings Center report, 2013)
The budget battles have hit the Indian Health Service hard: sequestration forced a 5 percent reduction in funds, followed by an additional 0.2 percent rescission in the recently passed Consolidated and Further Continuing Appropriations Act. Exempted from sequestration (and rightly so) were other very important health care programs such as the Veterans Administration Health Programs, the State Children's Health Insurance Programs, and Medicaid. Medicare has been reduced by only 2 percent, with that cut targeted to provider reimbursement so as to avoid a reduction in service to beneficiaries. In March 2013, Representatives Betty McCollum, Tom Cole, and Michelle Lujan Grisham introduced a bill to reduce the impact of sequestration on the IHS to 2 percent (H.R. 1371). This bill was referred to the Committee on the Budget, but to date, there has been no movement on it. Why was the IHS susceptible to sequestration? Why is it considered a “discretionary” line item in the federal budget? Why is there not parity for Indians, whose health status remains far below that of mainstream America? As a matter of legal requirement, social contract, and moral obligation, the United States should fundamentally change how Indian Health is funded.